2022
DOI: 10.3389/fimmu.2022.874064
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant IL-17 Levels in Rodent Models of Autism Spectrum Disorder: A Systematic Review

Abstract: Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental disorder characterised by stereotyped behaviours, specific interests, and impaired communication skills. Elevated levels of pro-inflammatory cytokines, such as interleukin-17A (IL-17A or IL-17), have been implicated as part of immune alterations that may contribute to this outcome. In this context, rodent models have helped elucidate the role of T-cell activation and IL-17 secretion in the pathogenesis of ASD. Regarding the preclinical findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The increased serum concentration of proinflammatory cytokines in the HTX-offspring is in concordance with ASD-like molecular features. Considering the neuroinflammatory component of ASD ( 47 ), IL-17A and its counterpart IL-10 were quantified in brain regions related to social cognition (prefrontal cortex (PFC) and hippocampus) ( Figure 7 , Supplementary Table 2-2.2 ). In the PFC, both female and male HTX-offspring had an increased concentration of IL-17A ( Figure 7A , Supplementary Table 2-2.2a ), while a reduction of IL-10 in the PFC was only observed in male HTX-offspring, compared to Control and HTX+T 4 offspring ( Figure 7B , Supplementary Table 2-2.2b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased serum concentration of proinflammatory cytokines in the HTX-offspring is in concordance with ASD-like molecular features. Considering the neuroinflammatory component of ASD ( 47 ), IL-17A and its counterpart IL-10 were quantified in brain regions related to social cognition (prefrontal cortex (PFC) and hippocampus) ( Figure 7 , Supplementary Table 2-2.2 ). In the PFC, both female and male HTX-offspring had an increased concentration of IL-17A ( Figure 7A , Supplementary Table 2-2.2a ), while a reduction of IL-10 in the PFC was only observed in male HTX-offspring, compared to Control and HTX+T 4 offspring ( Figure 7B , Supplementary Table 2-2.2b ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, anti-inflammatory cytokines like IL-10 and TGF-β1 are typically lower in ASD patients ( 45 , 46 ). Additionally, elevated concentration of IL-17A in specific brain regions, which is considered as a neuroinflammatory-like trait, is associated with alterations in social cognition and appears to be a signature outcome of ASD physiopathology according to animal models displaying ASD-like behaviors ( 47 ). Moreover, ASD-related inflammatory profile can be accompanied by persistent dysregulation of both innate and adaptive immune response, as indicated by murine models.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, and taking into consideration the association between neuroinflammatory traits and neurodevelopmental disorders [48,49], we quantified IL-17A and its counterpart IL-10 in the prefrontal cortex (PFC) and hippocampus of each experimental group (see Materials and methods) (Figure 7, SF 2.2), which are pivotal brain regions for social cognition and organization control [47,48]. In the PFC, we found that HTX-offspring (both sexes) had an increased concentration of IL-17A (Fig.…”
Section: Htx-offspring Display Inflammatory Traits That Exhibit Simil...mentioning
confidence: 99%
“…Males are notably more likely to develop ASD than females (3). Recent studies have proven that genetics, inflammatory response, oxidative stress, and hypoxic insult exert crucial roles in leading to ASD progression (4)(5)(6)(7). The specific pathological mechanisms underlying ASD remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%